MOTIVASI DAN TINGKAT PENERIMAAN LAYANAN ONLINE STREAMING DI BATAM - Avaleska Avaleska; Kendrik Jonatan, Kelvin, Johan, Frenkie Tan (ADISAM PUBLISHER, 2024)
This era is an era when television is no longer the first choice in the hearts of customers as a place to look for entertainment or the latest information. The internet can be accessed anywhere and anytime, causing television to become less attractive to teenagers compared to using technology that can access the internet. The practicality and ease of use of their smart TVs, smartphones or tablets to access online streaming services is the main reason for doing online streaming. The quantitative approach is the method that will be used for this research and the questionnaire will be distributed online. The sampling method applied in this research is cluster disproportionate random sampling. This analysis will be carried out by utilizing the SPSS and AMOS applications and applying the PLS-SEM approach to test the hypothesis. The results showed that Perceived Ease of Use had a significant and positive influence on Perceived Usefulness and Perceived Usefulness, Instrumental Use, and Ritualized Use had a significant and positive effect on Intention to Use. However, Perceived Ease of Use does not have a significant effect and can have a negative impact on Intention to Use. It is known that online streaming services in the aspect of ease of access and use really need improvisation, but other aspects still need to be considered so that they can complement and support each other